An Analysis of the Influence of Social Media on Direct and Indirect Illocutionary Speech Acts Among Students at Dhuhaa Islamic School - Yani, Juli; S, Ermawati .; Ridwan, Ridwan; Setyawati, Nanik; Muljani, Sutji (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This research aims to describe and inform about the influence of social media on the speech acts or behavior of students in an educational unit by looking at it based on direct illocution and indirect illocution. The data in this analysis are students in grades 4, 5 and 6 of SD Dhuhaa Islamic School. The primary data in this research are students' actions and speech related to direct locution and indirect illocution, while the secondary data are books or expert opinions related to the object of this research. This research is included in qualitative research. The data collection techniques used were interviews and observation. This research uses a content analysis method. Based on the research that has been carried out, it is concluded that there is an influence from the use of social media on the speech acts of students in grades 4, 5 and 6 at SD Dhuhaa Islamic School. This is because of the speech acts or behavior shown by these students, which are included in the influence of social media.